565. Implementing HIV Rapid Entry in a Community Infectious Disease Practice. (26th November 2018) - Cafardi, John; Lamarre, Thomas; Haas, Douglas; Young, Patricia; Stockton, Janice; Kallmeyer, Robert
Abstract: Background: Successful achievement of "90-90-90" HIV care continuum goals depends on increasing diagnosis, linkage to care, and treatment initiation. Recent improvement efforts include immediate linkage and antiretroviral (ARV) therapy access. Outcome data has been reported from projects implemented in academic settings where multiple Ryan White Care Act (RWCA) services are available. The purpose of this project was to assess feasibility of Rapid Entry in a four-physician community ID practice. Methods: Goals of the Rapid Entry project are: first visit within three business days of diagnosis and ARV start at entry. Outcomes assessed include time to first visit, ARV start, and virologic suppression. Retention in care is assessed at 6 and 12 months. Comparison is made to "standard of care" (SOC; n = 35) patients seen during 24 months prior to project implementation. Patients with new HIV diagnosis made while hospitalized were excluded. Results: Thirty-four patients with new HIV diagnosis started care during project period. Demographics and baseline labs were similar between groups. Four rapid patients were injection drug users (IDU) vs. none in SOC. Time to First visit averaged 13 days (range 1–48) with 12 patients (37%) seen within three business days (SOC 7–189 days, mean 36). 19 patients (56%) started ARVs at the First visit (SOC 1/3%); 23 (68%) by Day 7 (SOC 5/15%). Time to virologic suppression was significantly less in the Rapid group. Conclusion: Preliminary results are comparable to reports from larger studies, suggesting that reduced time to first visit and ARV initiation shortens interval to virologic suppression. Implementing Rapid Entry in a community setting is challenging but feasible, requiring high levels of staff commitment, flexibility, and communication. Efforts in process to further improve Rapid Entry include strategies to engage/retain those infected via injection drug use and shortening time to referral from outside test sites. Disclosures: J. Cafardi, Gilead: Grant Investigator, Salary.